Frontispiece: Controlled Modification of Axial Coordination for Transition‐Metal Single‐Atom Electrocatalyst. Issue 59 (25th October 2022) - Liu, Xiangjian; Liu, Yarong; Yang, Wenxiu; Feng, Xiao; Wang, Bo
Abstract : M−N−C single‐atom catalysts have emerged as a novel frontier in electrocatalysis. Their catalytic behavior is optimized by the lack of metal–metal bonds and ability to adjust the coordination configuration and electronic structure of their metal–heteroatom bonds. In particular, this concept discusses the importance of the axial coordination strategy toward single atom catalyst. For more details, see the Concept by B. Wang and co‐workers. (DOI: 10.1002/chem.202201471 ).